30. ANALYSIS OF SOME FACTORS RELATED TO TREATMENT COMPLIANCE OF PATIENTS WITH PEPTIC ULCER OF OUTPATIENT AT UNIVERSITY HOSPITAL OF MEDICINE AND PHARMACY, HANOI NATIONAL UNIVERSITY, 2023 (Vietnam Journal of Community Medicine, 2024)
Background: Peptic ulcer is a chronic disease with cyclical progression. The lesions are ulcers in the gastric and duodenal mucosa, these ulcers can invade deeper through the submucosa layer; ulcer location in the stomach (gastric ulcer) or in the duodenum (duodenal ulcer). Adherence to treatment helps improve treatment effectiveness and quality of life for patients. Objective: Analyze some factors related to treatment compliance of patients with peptic ulcer disease. Methods: Cross-sectional survey, quantitative research. Results and conclusion: The proportion of women (54.7%) is higher than that of men (45.3%), the age group over 50 years old accounts for 67%. The duration of the disease is over 5 years, accounting for 51.1%. As age increases, the rate of treatment compliance tends to increase: from 18.5% to 28% and 64% (p
Keywords: Adherence/acompliance to treatment, Peptic ulcer, patient, related factors.